Strengthening National Character in Facing Global Challenges - Anar Mella Aindini; Bima Satrya Alegra; Suparmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The advancement of technology and the rapid flow of digital globalization have brought enormous impacts on the way of life of the Indonesian nation. On the one hand, this development brings many benefits, such as ease of accessing information and expanding public knowledge. However, on the other hand, globalization also poses a serious challenge to the character and national identity. The free entry of foreign culture through digital media often makes the younger generation easily influenced by values that are not in line with the Indonesian national personality. This research aims to discuss the importance of strengthening national character in facing global challenges through the implementation of character education and culture-based education. The method used is a Systematic Literature Review (SLR) by examining various research results obtained through websites. Based on the study results, digital globalization is proven to influence the way people think, behave, and act, especially the younger generation, leading to the weakening of moral values, national spirit, and cultural identity. As a solution, character education combined with local cultural values is considered an important step to foster a generation that is moral, cultured, and able to compete in the global era. The roles of teachers, schools, families, and society are also very influential in instilling positive values in students. Culture-based education not only serves to preserve the nation's heritage but also becomes a means to adapt to the development of the times. Thus, through education that instills moral and cultural values and the wise use of technology, it is hoped that Indonesia will be able to produce a generation that is intelligent, of noble character, and remains proud of its national identity amidst the strong current of globalization.